Feasibility of struvite recovery process for fertilizer industry: A study of financial and economic analysis - Yetilmezsoy, Kaan; Ilhan, Fatih; Kocak, Emel; Akbin, Havva Melda (ELSEVIER SCI LTD, 2017)
Struvite precipitation is widely used as an established and promising physicochemical treatment method due to its higher effectiveness for removing and recovering excess nitrogen and phosphorus from wastewater, and production of a beneficial byproduct at the end of the process. However, the majority of the literature focus not on the economic aspects of the process, but rather on the effect of different chemical combinations and changing operating conditions. In order to fulfill this gap, this study aims at a comprehensive feasibility analysis of struvite recovery process for a full-scale fertilizer production industry with a 500 m(3)/day capacity. For quantitative assessment, the experimental conditions and chemical combinations that will allow the receiving environment discharge standard for ammonium nitrogen are optimized by taking into account a large number of economic and operating parameters. The effect of change in the struvite sale price on the profit share is examined for the optimum conditions, and the investment and operating costs are calculated by getting the latest up-to-date values from the market. It is determined that when the struvite sale price is raised to 560 sic/ton, the facility will obtain a net profit of sic 445.62/day, and be able to pay for itself in approximately six years. The findings of this study corroborate the economic feasibility of struvite recovery process as a clean and eco-friendly technology at the plant level for a sustainable nutrient management. Clearly, it appears likely that the struvite precipitation method will become more widespread in the future as an effective and nonpolluting process. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Ammonium nitrogen; Economic analysis; Fertilizer industry; Magnesium ammonium phosphate; Struvite; Synthetic wastewater; WASTE-WATER TREATMENT; PHOSPHORUS RECOVERY; SIMULTANEOUS REMOVAL; LANDFILL LEACHATE; NUTRIENTS REMOVAL; PRECIPITATION; NITROGEN; MANURE; CRYSTALLIZATION; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology